GERAKAN KUDETA DAN POLEMIK DI KESULTANAN BANTEN 1750-1752: English - Aris Muzhiat Aris; Iik Arifin Mansurnoor Iik (Kawalu: Journal of Local Culture, 2020)
This article aims to exploit the coup movement and power polemics that occurred in the Sultanate of Banten. The colonial politics of fighting against each other had succeeded in dividing the noble and religious elites in the palace of the Sultanate of Banten. Apart from that, the Coup Movement carried out by the noble elite Ratu Bagus Buang was a form of protest against Dutch colonial intervention in appointing a replacement for Sultan Zaenal Arifin as Ratu Syarifah. Queen Syarifah's policy of often excluding the noble elite from making policies and sending large amounts of pepper to the VOC, as well as her oppressive policies, have drawn protests from the common people and the nobility. The coup movement carried out by Ratu Bagus Buang had caused a serious polemic in the Sultanate of Banten which aimed to take over power from Ratu Syarifah and expel the VOC from Banten. This confirms that the Dutch colonial political strategy and the struggle for power that occurred in the Banten Sultanate from 1750-1752 have been the determinants of legal changes and social dynamics that gave rise to the existence of the Banten Sultanate.